From a Three-Dimensional Finite Element Analysis of Stress Distribution and Displacement to Design of Patient Lifting Equipment - M. Sakunsongbunsiri (2020)
© Published under licence by IOP Publishing Ltd. The patients with stroke, especially hemiplegia and paraplegia cases, need to be transferred whether from bed to wheelchair or wheelchair to bed and be transferred whether from wheelchair or bed to car or car to a wheelchair or bed while the patient is admitted to the hospital or stay at home. The accuracy of movement handling is required to be in accordance with the principles of physiology in order to increase the safety of patient moving. The utilization of patient lifting equipment will improve patient handling more efficiently for both patients and staff during health care. Patient-lifting equipment is absolutely helpful in lifting patient movement. The study on the analysis of stress distribution as well as the displacement of the device in the analysis of strength in the structure design is rarely found because of computer program limitations. For appropriate usage in each situation, it is important to apply a comprehensive understanding of principles of strength analysis to design patient-lifting equipment. The objective of the proposed research is to design a spreader bar of the patient lift equipment to support use for transferring from a wheelchair or bed to car or car to a wheelchair or bed. The details regarding concept design and analysing the strength of the structure is solved by finite element method (FEM) with a three-dimensional model. The simulated results obtained from the computational solution are investigated and validated against those obtained from the analytical solution. The study focuses attention on the effects of different angles of the spreader bar on the stress distribution and displacement at various points. It is found that the change in the angle adjustment of the spreader bar directly affects the change in the stress distribution, as well as displacement. The maximum stress distribution, as well as maximum displacement, are reduced when the degree increases. The obtained results can be a helpful information to use as the guideline to design a spreader bar of the patient- lifting equipment to transfer patients suitably under each situation.